A Stackelberg game in multi-period planning of make-to-order production system across the supply chain. (January 2018) - Chua, Felixter Leone S.; Vasnani, Neelesh N.; Pacio, Lance Brandon M.; Ocampo, Lanndon A.
Highlights: A game theoretic model in analyzing a production planning problem in a make-to-order supply chain is proposed. The production problem is specified in a planning horizon with multiple time periods. The vertical interaction within the supply chain is played as a leader-follower game to determine the Stackelberg equilibria. Multiple scenarios are investigated such as constant selling price, limited workforce, and safety stock considerations. Abstract: Mass customization becomes an emerging trend in numerous industries. With this, firms are adopting the make-to-order production strategy to allow ease of producing product varieties. This study adopts a game theoretic approach in analyzing a supply chain which consists of a manufacturer with multiple suppliers. The manufacturer has an exclusive supplier for every required component of its final product. The manufacturer may also consider for a third-party subcontractor to produce a fraction of its demand. The game is dynamic in nature wherein the interactions and decisions of the firms are observed in multiple time periods. Relevant to the make-to-order environment, price and lead time market elasticity are considered. The vertical interaction within the supply chain, between the manufacturer and its suppliers, is played as a leader-follower game. On the other hand, multiple scenarios are investigated such as constant selling price, limited workforce, and safety stock considerations to further provide managerial insights between the interactions of the supply chain members. In order to test the applicability of the proposed model, we present a case study of a local advertisement supply chain in the central Philippines. Finally, the results are interpreted to provide key managerial insights and conclusions.